2005
DOI: 10.1016/j.jada.2005.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dietary Supplement Use with Specific Micronutrient Intakes among Middle-Aged American Men and Women: The INTERMAP Study

Abstract: . (2005). Association of dietary supplement use with specific micronutrient intakes among middleaged american men and women: the INTERMAP study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 24 publications
9
52
1
1
Order By: Relevance
“…Results also showed that only workplace and vitamin C supplementations were significantly correlated with the motorized tricycle drivers' blood vitamin C levels (p<0.05) however, this study does not negate the possibility that the other factors or the conjunction of factors may play a significant influence on their blood vitamin C levels. The findings obtained is supported by that of Archer et al 7) that vitamin supplementations help contribute to the total nutrient intake of an individual. Simon and Hudes 8) likewise supports the findings in this study that the low levels of blood vitamin C evident among the motorized tricycle drivers may be influenced by their environment particularly their workplace conditions.…”
supporting
confidence: 80%
“…Results also showed that only workplace and vitamin C supplementations were significantly correlated with the motorized tricycle drivers' blood vitamin C levels (p<0.05) however, this study does not negate the possibility that the other factors or the conjunction of factors may play a significant influence on their blood vitamin C levels. The findings obtained is supported by that of Archer et al 7) that vitamin supplementations help contribute to the total nutrient intake of an individual. Simon and Hudes 8) likewise supports the findings in this study that the low levels of blood vitamin C evident among the motorized tricycle drivers may be influenced by their environment particularly their workplace conditions.…”
supporting
confidence: 80%
“…Since the FFQ has good ability to rank individuals according to relative nutrient intakes, the misreporting may not be problematic in the present study (21,22) . Vitamin and mineral supplement usage was not taken into account; but this may not influence the results however, since supplement users are likely also to have higher vitamin intakes from foods and thus be classified correctly (50)(51)(52) . Furthermore, the FFQ overestimates energy intake compared with diet records, but the results at the group level were found to be satisfactory, and all nutrient intake levels were corrected with energy intake, using the residual method (31) .…”
Section: Discussionmentioning
confidence: 99%
“…A survey of men and women 51 years and older found that trying to follow a healthful diet was the most consistent reason given for the use of vitamin and mineral supplements (Sebastian et al 2007). Higher levels of some nutrients were also associated with supplements (Archer et al 2005).…”
Section: Promoting Improved Quality Of Lifementioning
confidence: 94%